Analysis of global DNA methylation and epigenetic modifiers (DNMTs and HDACs) in human foetal endothelium exposed to gestational and type 2 diabetes. Issue 1 (31st December 2023) - Sultan, Samar; AlMalki, Sultanh
ABSTRACT: Foetuses exposed to maternal gestational diabetes (GDM) and type 2 diabetes (T2D) have an increased risk of adverse perinatal outcomes. Epigenetic mechanisms, including DNA methylation and histone modifications, may act as mediators of persistent metabolic memory in endothelial cells (ECs) exposed to hyperglycaemia, even after glucose normalization. Therefore, we investigated alterations in global DNA methylation and epigenetic modifier expression (DNMT1, DNMT3a, DNMT3b, HDAC1, and HDAC2) in human umbilical vein ECs (HUVECs) from the umbilical cords of mothers with GDM ( n = 8) and T2D ( n = 3) compared to that of healthy mothers ( n = 6). Global DNA alteration was measured using a 5-methylation cytosine colorimetric assay, followed by quantitative real-time polymerase chain reaction to measure DNA methyltransferase and histone acetylase transcript expression. We revealed that DNA hypermethylation occurs in both GDM- and T2D-HUVECs compared to that in Control-HUVECs. Furthermore, there was a significant increase in HDAC2 mRNA levels in GDM-HUVECs and increase in DNMT3b mRNA levels in T2D-HUVECs. Overall, our results suggest that GDM and T2D are associated with global DNA hypermethylation in foetal endothelial cells under normoglycemic conditions and the aberrant mRNA expression of HDAC2 and DNMT3b could play a role in this dysregulation. Key policy highlights: Global DNA hypermethylation was reported in foetal endothelial cells of both gestational and type 2 diabetes cultured under normal glucose condition HDAC2 mRNA was significantly increased in gestational diabetes DNMT3b mRNA was significantly increased in type 2 diabetes Our data support the concept of epigenetic programming occurs in foetal endothelial cells exposed to diabetes which retain even after glucose normalization